France in the world : the career of André Siegfried - Kennedy, Sean, 1969- (McGill-Queen's University Press, 2023)
"André Siegfried (1875-1959) was a leading figure in French academic and cultural life for over five decades. A world traveller who trained as a geographer, Siegfried became a leading political scientist and prominent newspaper columnist. As a long-time professor at Sciences Po, he shaped generations of his country's elite. France in the World explores the life and career of André Siegfried. An innovator in the field of political science, he established himself as France's leading interpreter of the English-speaking world. Often likened to Alexis de Tocqueville, Siegfried published influential studies of the United States, Canada, Great Britain, and New Zealand, striving to understand France's place in a changing global context. Siegfried was a cosmopolitan promoter of liberalism and individual freedom. But at the same time he perceived France to be the core of a Western civilization whose leadership and values were threatened by Americanization, anti-imperial nationalism, and non-white immigration. By following Siegfried's long career and examining the breadth of his writings, Sean Kennedy shows how his racial and ethnic essentialism was a unifying aspect of his life's work. That these ideas were considered unremarkable for most of his lifetime offers a powerful illustration of how racist thinking permeated mainstream French republicanism. Exploring the many facets of Siegfried's career, France in the World examines the entanglement of liberal and racist thinking during an era that witnessed political extremism and a rapidly changing international order."--